Effectiveness of an Educational Module on Diet and Nutrition: A Farm Women Perspective from Aspirational Districts - Dominic, Ditty Maria; Meena, H. R.; Niranjan, D. Alagu (Indian Journal of Extension Education, 2022)
Farm women, although they play a significant role in food and nutritional security of their households, are very much deprived of knowledge and information on food and nutrition. Only few studies have focused on nutrition of farm women and no studies have been found on farm women in aspirational districts in particular. Hence, in the present cross sectional study conducted in 2021, an educational module (folder) entitled “Diet and Nutrition of Farm Women: A Short Guide” was developed in Tamil, Malayalam and English. The module’s contents were subjected to relevancy test by 30 experts. The module’s effectiveness as perceived by the respondents on six characteristics were measured using a 19 item scale developed based on Guidelines for Pretesting and Evaluating Communication Materials given by Ministry of Health, Zambia. Responses were taken from 60 farm women to assess their perception on effectiveness of the module. Nearly 70 per cent of the farm women perceived that the educational module was useful. Majority perceived that the contents were interesting and they will follow the suggestions in the module. Hence, perceived effectiveness of the developed educational module was high and it can be used to impart behavioural change among farm women under similar circumstances.
Keywords: Farm women; Diet; Nutrition education; Educational module; Effectiveness; Aspirational districts